2017
DOI: 10.1159/000454990
|View full text |Cite
|
Sign up to set email alerts
|

Adenine Rich Diet Is Not a Surrogate of 5/6 Nephrectomy in Rabbits

Abstract: Background: Animal models are important tools needed to understand the mechanisms underlying the progression of renal disease and to implement new therapeutic approaches. A non-surgical model of chronic kidney disease (CKD) developed by chemical nephrectomy using an adenine-enriched diet has been shown to be a robust model to induce kidney failure in mice and rats. The purpose of this study was to implement an adenine diet to induce CKD in rabbits. Methods: Male New Zealand rabbits were fed for 4 weeks with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(44 reference statements)
1
6
1
Order By: Relevance
“…Nevertheless, Aoyama et al [65] has shown that adenine (0.75% w/w) in the diet produced renal damage resembling CKD but also found 50% mortality. Thus, in the present study, we used adenine at the dose of 0.75% w/w in the diet for 24 days and no mortality was found which is consistent with previous reports [6164]. Furthermore, biochemical evaluations in our study have shown that distinctive CKD was produced in rats upon feeding with adenine.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, Aoyama et al [65] has shown that adenine (0.75% w/w) in the diet produced renal damage resembling CKD but also found 50% mortality. Thus, in the present study, we used adenine at the dose of 0.75% w/w in the diet for 24 days and no mortality was found which is consistent with previous reports [6164]. Furthermore, biochemical evaluations in our study have shown that distinctive CKD was produced in rats upon feeding with adenine.…”
Section: Discussionsupporting
confidence: 90%
“…Excess adenine in mammalian metabolism becomes a significant substrate for xanthine dehydrogenase and oxidises into low soluble compounds 2, 8-dihydroxyadenine which further precipitate in renal tubules and damage the kidney tissue accompanied by oxidative stress and subsequently renal dysfunction [60]. The adenine model is reproducible, simpler to conduct and more like human CKD than the 5/6 nephrectomy [61, 62]. Adenine-induced renal damage is time-dependent-the longer the feeding time, the more severe the renal damage [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study using 5/6 nephrectomy model has remained the developed prototype which closely mimics human CKD and is a useful model for studying drug responses in CKD. In contrast to what was observed in 5/6 nephrectomy, adenine diet failed to induce kidney failure in rabbits as is evident in functional indices in a recent study (Florens et al, 2017[ 18 ]). In the current study, we investigated the effects of H 2 S on CKD induced by 5/6 Nx in different dose, administration method and longer time in rats.…”
Section: Discussioncontrasting
confidence: 56%
“…Adenine and its metabolite, 2,8‐dihydroxyadenine, have a low solubility and precipitate in the renal tubules leading to their occlusion , resulting in inflammation accompanied by oxidative stress and subsequently renal dysfunction . The adenine model is more reproducible, simpler to conduct and more similar to human CKD than the 5/6 nephrectomy . The beneficial action of curcumin occurred in a dose‐dependent manner and encompassed markers of acute as well as of chronic renal damage.…”
Section: Discussionmentioning
confidence: 99%